Stochastic approximation procedure with impulsive Markov perturbations - Chabanyuk, Ya.M.; Semenyuk, S.A. (Математичне та комп'ютерне моделювання. Серія: Фізико-математичні науки, 2011)
In this paper we discuss asymptotic behavior of the stochastic approximation procedure in case when the regression function is perturbed by the Markov impulsive process. Also we consider the stochastic approximation procedure stability conditions in the terms of existence of Lyapunov's function for the averaged evolution system.